2011
DOI: 10.1182/blood-2011-03-341560
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals germline NPAT mutation as a candidate risk factor for Hodgkin lymphoma

Abstract: A strong clustering of Hodgkin lymphoma in certain families has been long acknowledged. However, the genetic factors in the background of familial Hodgkin lymphoma are largely unknown. We have studied a family of 4 cousins with a rare subtype of the disease, nodular lymphocyte predominant Hodgkin lymphoma.We applied exome sequencing together with genome-wide linkage analysis to this family and identified a truncating germline mutation in nuclear protein, ataxiatelangiectasia locus (NPAT) gene, which segregated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 37 publications
0
41
1
Order By: Relevance
“…37 Interestingly, we did not find shared variants in the three genes (KLHDC8B, NPAT, and ACAN) previously identified in high-risk HL families, [16][17][18] while we observed the POT1 rs202187871 variant also reported in a high-risk melanoma family. 20 Given the large total number of genes (2383) with family-shared variants that we identified, we also conducted pathway analyses using two independent tools, Ingenuity Variant Analysis (IVA) 38 Supplementary Table S6F).…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…37 Interestingly, we did not find shared variants in the three genes (KLHDC8B, NPAT, and ACAN) previously identified in high-risk HL families, [16][17][18] while we observed the POT1 rs202187871 variant also reported in a high-risk melanoma family. 20 Given the large total number of genes (2383) with family-shared variants that we identified, we also conducted pathway analyses using two independent tools, Ingenuity Variant Analysis (IVA) 38 Supplementary Table S6F).…”
contrasting
confidence: 47%
“…16 Recently, a mutation in the NPAT gene was identified in an extended pedigree segregating for the less common nodular lymphocytic predominant subtype of HL. 17 A homozygous deletion in the ACAN gene was identified in 3 siblings with classical HL. 18 We conducted a genome-wide linkage study in 44 HL families that revealed several regions of the genome possibly linked to HL, 19 but no susceptibility genes were subsequently identified.…”
mentioning
confidence: 99%
“…62,69 Lastly, certain germline polymorphisms of IL-10, IL-6, and NPAT may be associated with poorer prognosis (IL-10 and IL-6) or risk of development of nodular lymphocyte-predominant Hodgkin lymphoma (NPAT). 71 Several challenges arise, however, as we try to turn these interesting biological observations into clinically relevant biomarkers. Most problematic is the lack of wide validation of the significance of these biomarkers, which typically have been demonstrated in only small series of selected patients and have not been reproducibly shown to be significant in multiple independent series of patients.…”
Section: Risk Factors Reflecting Specific Biologic Characteristicsmentioning
confidence: 99%
“…Saarinen and colleagues combined 2 modern genetic methods, single nucleotide polymorphism chips and whole exome sequencing, and applied them to a unique Finnish family with 4 cousins all presenting from 22-26 years of age with NLPHL. 1 A germ line mutation in the NPAT (nuclear protein, ataxia-telangiectasia locus) gene was found in all 4 patients (see figure). The mutation was a 2 base pair deletion causing a frame shift and in consequnce a truncation of the protein.…”
mentioning
confidence: 96%
“…Cells from patients with NPAT mutations indeed showed reduced expression levels of the gene. 1 NPAT germ line mutations were found in NLPHL as well as in classic HL cases, suggesting that such mutations may contribute to the pathogenesis of both subtypes of Hodgkin lymphoma. This is a remarkable finding, because although classic and NLPHL are considered 2 forms of 1 disease, there is presently little indication for common genetic lesions or other shared transforming events in the tumor cells of these lymphomas.…”
mentioning
confidence: 99%